Penerapan E-Budgeting Untuk Mendukung Transparansi Anggaran Studi Kasus: Pemerintah Kota Surakarta - Sanjaya, Natta; Dewi, Hilandri; Putri, Selvi Septiana; Putri, Sendy Himalia; Nasya D, Abhista; Rini, Mutiara (ANTASENA: Governance and Innovation Journal, 2025)
This study aims to examine the implementation of the e-Budgeting system in supporting transparency and accountability in regional financial management, using the Government of Surakarta City as a case study. The research method employed is a literature review by analyzing various relevant academic sources on the implementation of e-Budgeting in public financial governance. The findings indicate that the application of e-Budgeting in Surakarta has improved administrative efficiency, strengthened budget transparency, and encouraged public participation through open access to financial information. This success is supported by competent human resources, adequate technological infrastructure, and strong managerial commitment. However, challenges such as cybersecurity threats, potential system viruses, and low digital literacy among the public remain significant issues. In conclusion, e-Budgeting is a vital innovation for realizing good governance and should be adopted by other regional governments as part of a modern and accountable financial reform effort.